2006
DOI: 10.2298/sarh0604114m
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic pseudoaneurysms

Abstract: Anastomotic pseudoaneurysm is a form of false aneurysm, whose wall does not consist of all normal layers of arterial wall. Given the rising number of reconstructive vascular procedures, the increase of anastomotic pseudoaneurysm cases is expected. Therefore, identification of causes, clinical manifestations as well as factors which affect the outcome of operative treatment of anastomotic pseudoaneurysms is of great practical value. This retrospectively-prospective study included 87 surgically treated cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Our patient presented with compressive symptoms and unremitting pain. As reported by Marković et al [1], compressive symptomatology compromises only 10% of presenting patients. Other presentations include acute and chronic limb ischemia, bleeding secondary to rupture and an asymptomatic pulsatile mass [1].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our patient presented with compressive symptoms and unremitting pain. As reported by Marković et al [1], compressive symptomatology compromises only 10% of presenting patients. Other presentations include acute and chronic limb ischemia, bleeding secondary to rupture and an asymptomatic pulsatile mass [1].…”
Section: Discussionmentioning
confidence: 83%
“…As reported by Marković et al [1], compressive symptomatology compromises only 10% of presenting patients. Other presentations include acute and chronic limb ischemia, bleeding secondary to rupture and an asymptomatic pulsatile mass [1]. Although the majority of PA is secondary to trauma or iatrogenic injury, other etiologic factors are postoperative infection, suture fatigue, poor suture material, postoperative nicotine use, recurrent operations to the same site and mechanical obstruction [7].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Most patients presented between 2 and 5 years after the initial operation and were treated with open repair. Furthermore, only 12.6% of patients presented after 10 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…The timeframe for development of anastomotic pseudoaneurysms varies based on study but is reported between 5 and 9.2 years after primary operation [7, 10]. Skourtis et al in their case series of 49 patients with anastomotic pseudoaneurysms reported that mean time of pseudoaneurysm developed to be 6.8 years [2].…”
Section: Discussionmentioning
confidence: 99%